Making cities work for all. - (:unkn) unknown (My University, 2016)
Cities are places where opportunities for prosperity coexist with stark inequalities between the richest and the poorest. Cities produce and attract highly educated workers and innovative employers. It is usually easier in cities than in other parts of the country for individuals to climb up the income, education or jobs ladder. But cities, especially the largest ones, also concentrate inequalities, both in income and in other well-being aspects, that remain remarkably high in many OECD economies. Access to opportunities seems stalled for many low-income urban residents, who often live in distressed neighbourhoods. This report provides ground-breaking, internationally comparable data on economic growth, inequalities and well-being at the city level in OECD countries. It provides empirical evidence on how cities are diverging from, or converging with, other parts of the country, and of the extent of inequality within cities. Finally, it proposes a framework for action, to help national and local governments reorient policies towards more inclusive growth in cities a new approach to growth that ensures that no part of society is left behind.
Keywords: Stadt; Gemeinde; Regionalwirtschaft; Wirtschaftswachstum; Beschäftigung; Lebensbedingungen; Einkommensverteilung; Segregation; Wachstumspolitik; Kommunale Wirtschaftspolitik; Lokale Wirtschaft; Inklusion; Lokale Ökonomie; Soziale Partizipation; Soziale Ungleichheit